1993
DOI: 10.1177/106002809302700301
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitol Content of Selected Oral Liquids

Abstract: A total of 129 products (98 chemical entities) were reviewed. Fifty-four (42 percent) of the products examined contained sorbitol. The frequency of sorbitol presence by liquid type was: solutions (33 percent), suspensions (43 percent), syrups (59 percent), elixirs (43 percent), concentrates (67 percent), drops (33 percent), tinctures (0 percent), and emulsions (0 percent). The percentage of listings indicating the presence of sorbitol was: manufacturer's product information (79 percent), Facts and Comparisons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…This result was consistent with the results of the study by Johnston where paracetamol-containing products were reported to have highest amount of sorbitol (16). Another study by Lutomski indicated that two forms of the same drug (paracetamol solution and elixir) had differences in their sorbitol content (14); in our study, it was observed that active components of drugs manufactured by different companies have different sorbitol contents; therefore, the total daily amount of sorbitol in drugs should be considered and switching to the counterpart with lower sorbitol content may be necessary at certain instances. Only three pharmaceutical brands containing higher amount of sorbitol that were identified in this study were included in the top 100 drug list of IMS-2014; however, this document included and sorted all dosage forms (solid and liquid dosage forms) marketed in Turkey.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result was consistent with the results of the study by Johnston where paracetamol-containing products were reported to have highest amount of sorbitol (16). Another study by Lutomski indicated that two forms of the same drug (paracetamol solution and elixir) had differences in their sorbitol content (14); in our study, it was observed that active components of drugs manufactured by different companies have different sorbitol contents; therefore, the total daily amount of sorbitol in drugs should be considered and switching to the counterpart with lower sorbitol content may be necessary at certain instances. Only three pharmaceutical brands containing higher amount of sorbitol that were identified in this study were included in the top 100 drug list of IMS-2014; however, this document included and sorted all dosage forms (solid and liquid dosage forms) marketed in Turkey.…”
Section: Discussionsupporting
confidence: 82%
“…Reported dose-related GI side effects were generally applicable in adult and intensive care unit population where patients present heterogeneous metabolic and nutritional status and polypharmacy (5-7); however, there were not many studies undertaken in pediatric population (8)(9)(10)(11)(12)(13). This problem was also noted in pediatric patients; a 5-year-old child who received valproic acid syrup has been reported to develop diarrhea because of the sorbitol content (9 g/day) of the drug, and the diarrhea resolved within 24 h after the dosage form was changed (14).…”
Section: Introductionmentioning
confidence: 99%
“…A minimally tolerable dose of sorbitol has not been established, but the potential to induce diarrhoea is substantial. Even though there is no guideline regarding the amounts of sorbitol that can cause adverse gastrointestinal effects, single doses of greater than 10 g and total daily dosages of greater than 50 g may produce adverse gastrointestinal effects in adult patients [7,13]. Children receiving sorbitol may tolerate smaller dosages than adults [13].…”
Section: Discussionmentioning
confidence: 98%
“…Sorbitol is abundantly present in the amantadine hydrochloride and propranolol preparations as well as the acetaminophen solutions this patient received prior to the onset of her gastrointestinal symptoms [13]. In the assessment of enteral abnormalities, all components of medications, active and 'inactive', must be evaluated as possible aetiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sorbitol is occasionally used as an osmotic laxative in doses of 7.5 to 30 g. Sorbitol frequently causes bloating and flatulence with daily doses of 10 g and abdominal cramps occur with 20 g per day. 6 While individual preparations contain relatively small amounts, patients receiving multiple medications in maximum doses are more likely to experience diarrhea, which can result in serious morbidity. 7…”
Section: Small Bowel Transitmentioning
confidence: 99%